2015
DOI: 10.1523/jneurosci.1625-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Posture on Brain Glymphatic Transport

Abstract: The glymphatic pathway expedites clearance of waste, including soluble amyloid ␤ (A␤) from the brain. Transport through this pathway is controlled by the brain's arousal level because, during sleep or anesthesia, the brain's interstitial space volume expands (compared with wakefulness), resulting in faster waste removal. Humans, as well as animals, exhibit different body postures during sleep, which may also affect waste removal. Therefore, not only the level of consciousness, but also body posture, might affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
277
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(321 citation statements)
references
References 49 publications
12
277
3
7
Order By: Relevance
“…Acute CMc is suited for combination with 2-photon imaging, which provides detailed information about glymphatic activity within cortex to a depth of approximately 200 µm 1,2 . Importantly, acute CMc also affords the advantage of supporting unbiased MRI studies, where tracer distribution is followed dynamically, relative to an individual baseline image acquired before the initiation of CSF tracer injection 15,16,17 . For MRI, the dental needle used for CMc should be replaced by a borosilicate capillary (approximately 1 cm length, tip diameter of approximately 20 µm) attached to the PE tubing.…”
Section: Discussionmentioning
confidence: 99%
“…Acute CMc is suited for combination with 2-photon imaging, which provides detailed information about glymphatic activity within cortex to a depth of approximately 200 µm 1,2 . Importantly, acute CMc also affords the advantage of supporting unbiased MRI studies, where tracer distribution is followed dynamically, relative to an individual baseline image acquired before the initiation of CSF tracer injection 15,16,17 . For MRI, the dental needle used for CMc should be replaced by a borosilicate capillary (approximately 1 cm length, tip diameter of approximately 20 µm) attached to the PE tubing.…”
Section: Discussionmentioning
confidence: 99%
“…Here, using dynamic-contrast-enhanced MRI, it was found that there was lower interstitial solute retention and improved clearance when mice were placed in the lateral decubitus position compared to either prone or supine positions (39). Further, it was demonstrated that there was enhanced fluorescent CSF tracer influx to the cerebrum when mice were placed in the lateral position relative to being prone (39). Thus, it is clear that postural or gravitational factors also exert regulatory control over the glymphatic pathway.…”
Section: The Glymphatic System – a Pathway For Csf-isf Exchangementioning
confidence: 99%
“…Following traumatic brain injury, reduced clearance of cortical interstitial solute was associated with motor and cognitive neurological deficits (26). While CSF-ISF exchange within the glymphatic pathway is improved by increased cerebral penetrating arterial pulsatility (27), the sleep state (20), and a lateral head position during sleep (28), none of these regulatory factors have yet been demonstrated to improve waste clearance in any of the above disease states. Consequently, a critical area of future glymphatic research is identification of novel mechanisms to control flow through this pathway with the goal of modifying diseases characterized by toxic extracellular solute accumulation.…”
Section: The Glymphatic System: Anatomy and Function In Health And DImentioning
confidence: 99%